Geochemistry and petrogenesis of Narnaul Pegmatites in Delhi Supergroup rocks, Narnaul Area, Southern Haryana, India - Kanyan, Naveen Kumar; Kumar, Naresh; Chaudhri, A. R.; Kumar, Naveen (Journal of Nepal Geological Society, 2020)
Metasedimentary rocks of Delhi Supergroup (900-1600 Ma; latitude 28°2΄ - 28°7N΄ and longitude 76°3΄ - 76°7΄ E) are exposed in the Aravalli Mountain (South of Haryana State). The metasedimentary rocks are mainly quartzite with lesser amount of schist, granitic gneiss, basic rocks, calc rocks, phyllite, slate, granite, pegmatite and veins of quartz. Most of the pegmatites of the study area intruded into the quartzite. Pegmatites occur as irregular masses, dyke swarms, branching dykes, criss-cross veins and elongated lenses. They strike in NNE direction with low dip angle. Their dimensions are variable (0.5 m - 250 m length and 0.5 - 100 m width). Narnaul pegmatites are very coarse grained and consist of quartz (smoky, milky, yellowish brown, buff), orthoclase, albite, biotite, muscovite, tourmaline, calcite, beryl, garnet, hornblende and natrolite in the decreasing order of abundance. Pegmatitic, hypidiomorphic and granophyric textures are observed in them. Model analyses data of the pegmatites is plotted mainly in the field of granite, alkali granite and quartz rich granitoid fields of QAP diagram. The studied granitoids belong to calc-alkaline-granodiorite series which were generated by crustal fusion process. Geochemically, the pegmatites are high in SiO2, Al2O3, K2O, Rb, Zr, Cs, Ta, Pb, P and Y and low in CaO, K, U, Th, Ti, Ba, Sr, Nb and Nd. These characters attest them as peraluminous, I-type and they are formed in post-orogenic tectonic settings. Petrogenetic modeling studies indicate that these pegmatites could have been derived by 30% partial melting of crustal source rock occurring in the region.